Eating clean for dummies - Wright, Jonathan V.; Larsen, Linda Johnson (For dummies., 2016)
Used as a way of life, clean eating can improve overall health, prevent disease, increase energy and stabilize moods. Provides the reader with an-easy-to-follow guide to eliminate processed foods from one's diet and improve one's health and budget by eating clean--Source other than Library of Congress.